Low-dose in utero exposure to finasteride promotes developmental changes in both male and female gerbil prostates - Maldarine, Juliana S.; Sanches, Bruno D. A.; Santos, Vitória A. [UNESP]; Amaro, Gustavo M. [UNESP]; Calmon, Marília F. [UNESP]; Rahal, Paula [UNESP]; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastião R. [UNESP] (My University, 2019)
The prostate is an accessory reproductive gland that is sensitive to the action of exogenous compounds known as endocrine disrupters that alter normal hormonal function. Finasteride is a widely used chemical that acts to inhibit the conversion of testosterone in its most active form, dihydrotestosterone. It is known that intrauterine exposure to finasteride causes changes in the male prostate even at low dosages; however, it is not known whether these dosages are capable of causing changes in the female prostate, which is present in a large number of mammalian species, including humans. In the present study, histochemistry, immunohistochemistry, immunofluorescence, serological dosages, and three-dimensional reconstruction techniques were employed to evaluate the effects of intrauterine exposure to a low dose of finasteride (100 μg.BW/d) on postnatal prostate development in male and female Mongolian gerbils. The results indicate that the gerbil female prostate also undergoes alterations following intrauterine exposure to finasteride, exhibiting a thickening of periductal smooth muscle and increased stromal proliferation. There are also intersex differences in the impact of exposure on the expression of the androgen receptor, which was increased in males, and of the estrogen-α receptor, which was decreased in the male prostate but unchanged in females. Altogether, this study indicates there are sex differences in the effects of finasteride exposure even at low dosages.
Keywords: androgen receptor; estrogen receptor; female prostate; finasteride; gerbil; intrauterine exposure; low-dose exposure; smooth muscle